The Effect of Intellectual Capital and Digital Transformation on Financial Performance in Technology Companies in Indonesia for the Period 2022 to 2025 - Tiara Cinta Putri Mardani; Tri Gunarsih (Journal Research of Social Science, Economics, and Management, 2026)
The rapid advancement of digital technology has encouraged technology companies to strengthen their strategic resources and digital capabilities to enhance financial performance. Intellectual capital and digital transformation have become increasingly important factors in developing competitive advantages through effective knowledge management, innovation, operational efficiency, and value creation. This study aimed to examine the effects of intellectual capital and digital transformation on the financial performance of technology-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2025 period. The study employed a quantitative approach using secondary data obtained from the annual reports and audited financial statements of 30 technology companies. The sample was selected using purposive sampling, resulting in a balanced panel dataset comprising 120 firm-year observations. Intellectual capital was measured using the Value Added Intellectual Coefficient (VAIC™) method, digital transformation was proxied by the ratio of intangible assets to total assets, and financial performance was measured using return on assets (ROA) and return on equity (ROE). The data were analyzed using panel data regression in EViews. The results indicated that intellectual capital and digital transformation had positive and statistically significant effects on both ROA and ROE. Firm size, included as a control variable, also had a positive and statistically significant effect on financial performance. These findings indicate that effective management of intellectual capital and investment in intangible resources associated with digital transformation play important roles in enhancing profitability and sustaining the competitiveness of technology companies in Indonesia.